Teen-Size Humanoid âFLoWâ Complete Analytical Kinematics - Yanto, Luky; Dewanto, Raden Sanggar; Pramadihanto, Dadet; Binugroho, Eko Henfri (EMITTER International Journal of Engineering Technology, 2017)
Humanoid research in Indonesia is quite a lot, but in reality only limited in kid-size proportional size, while for the Teen-Size is still rare. Research on the Teen-Size Humanoid robot requires more joints to be able to perform the movement compared to the size of Kid-Size, therefore required more complex modeling to determine the movement. With complete kinematics anlysis, the movement of the robot can be solved. With kinematic forward-invers, researchers can determine the movement of robots by controlling the motor parts that function as a joint on the robot. In this study, the modeling uses D-H parameter, because this modeling has been widely used, besides the calculation can be solved by computing. And then for the simulation can be done with V-REP software. Forward-invers kinematics can be implemented on the PID algorithm, in order to generate speed on the motor that can form an angle on the motor to make the movement. The result of this research is to obtain equation of matrix transformation from all body parts of robot. With the creation of this Humanoid Teen-Size robot, it is hoped that the research on Humanoid robot in Indonesia will be increasingly diverse and increasing, and can be used as a support and reference in the development of Humanoid Teen-Size next.